Tsunamigenic potential of a newly discovered active fault zone in the outer Messina Strait, Southern Italy. Issue 5 (15th March 2017) - Fu, Lili; Heidarzadeh, Mohammad; Cukur, Deniz; Chiocci, Francesco L.; Ridente, Domenico; Gross, Felix; Bialas, Jörg; Krastel, Sebastian
Abstract: The 1908 Messina tsunami was the most catastrophic tsunami hitting the coastline of Southern Italy in the younger past. The source of this tsunami, however, is still heavily debated, and both rupture along a fault and a slope failure have been postulated as potential origin of the tsunami. Here we report a newly discovered active Fiumefreddo‐Melito di Porto Salvo Fault Zone (F‐MPS_FZ), which is located in the outer Messina Strait in a proposed landslide source area of the 1908 Messina tsunami. Tsunami modeling showed that this fault zone would produce devastating tsunamis by assuming slip amounts of ≥5 m. An assumed slip of up to 17 m could even generate a tsunami comparable to the 1908 Messina tsunami, but we do not consider the F‐MPS_FZ as a source for the 1908 Messina tsunami because its E‐W strike contradicts seismological observations of the 1908 Messina earthquake. Future researches on the F‐MPS_FZ, however, may contribute to the tsunami risk assessment in the Messina Strait. Key Points: A new fault zone named Fiumefreddo‐Melito di Porto Salvo Fault Zone is discovered in the outer Messina Strait, Southern Italy A 60 m high escarpment at the seafloor characterizes this fault zone as the most prominent active feature in the outer Messina Strait Numerical modeling revealed that this fault zone can generate tsunami amplitudes exceeding 2 m by assuming a fault slip of 5 m